Blending Modification of PHBV/PBS/PEG and its Biodegradation. Issue 10 (3rd July 2017) - Hu, Xueyan; Liu, Huifang; Gao, Zhaoying; Su, Tingting; Wang, Zhanyong; Yang, Lei
ABSTRACT: This study used poly(butylene succinate) and poly(ethylene glycol) to modify poly(3-hydroxybutyrate- co -3-hydroxyvalerate). The results showed that the incorporation of poly(butylene succinate) and poly(ethylene glycol) improved the mechanical properties of blends. The results showed that crystallinity of the poly(ethylene glycol)-containing blends decreased, so do the crystallization temperature and melting temperature of the poly(3-hydroxybutyrate- co -3-hydroxyvalerate) component of blends. Poly(butylene succinate)/poly(3-hydroxybutyrate- co -3-hydroxyvalerate)/poly(ethylene glycol) ratio of 50:20:30 was chosen owing to its good properties. The poly(3-hydroxybutyrate- co -3-hydroxyvalerate) component of blends can be degraded completely by Pseudomonas mendocina DS04-T, whereas this strain cannot degrade poly(butylene succinate) and poly(ethylene glycol). Apart from poly(butylene succinate), Fusarium sp. FS1301 can also biodegrade poly(3-hydroxybutyrate- co -3-hydroxyvalerate) and poly(ethylene glycol). GRAPHICAL ABSTRACT: